Improved Output Performance of Triboelectric Nanogenerator by Fast Accumulation Process of Surface Charges. Issue 14 (4th March 2021) - Li, Yanhong; Zhao, Zhihao; Liu, Lu; Zhou, Linglin; Liu, Di; Li, Shaoxin; Chen, Shengyang; Dai, Yejing; Wang, Jie; Wang, Zhong Lin
Abstract: As a promising energy harvesters, triboelectric nanogenerators (TENG) can be utilized to convert distributed energy into electric power, but the slow charge accumulation incorporated with the inevitable charge decay/leakage of conventional TENGs result in a low surface charge density and an inferior output performance, limiting their practical applications. Here, an effective strategy is proposed to realize high charge density by using a fast charge accumulation process on dielectric material with high relative permittivity. As a result, the charge density is tremendously improved to 2.20 mC m −2 on the poly(vinylidene fluoride‐trifluoroethylene) film. Meanwhile, the fast charge accumulation is highly conducive to reach a high charge density of 1.30 mC m −2 in a 90% relative humidity environment, which is ≈260 times that of a TENG with slow charge accumulation. This work not only provides a new insight into charge accumulation and equilibrium state, but also provides significant guidance on the performance optimization of TENG. Abstract : A fast charge accumulation process on a dielectric material with high relative permittivity is demonstrated to be extremely conducive to improve the charge density of a triboelectric nanogenerator. This work not only raises the equilibrium state of surface charges, but also provides significant guidance on the performance optimization of triboelectric nanogenerators.